PENGARUH BIOKOAGULAN DARI KULIT PISANG KEPOK DAN BIJI KELOR TERHADAP KUALITAS LIMBAH CAIR INDUSTRI TAHU - Ba'adilla, Syukma; Nugraha, Aditya Wahyu; Laksono, Untung Trimo (PPPM POLTESA, 2025)
Tofu wastewater contains highly organic compounds such as proteins, fats, and carbohydrates. Without proper treatment, it can cause negative environmental impacts such as groundwater ecosystem disruption, unpleasant odors, and a source of disease. Coagulation-flocculation was one of the methods that could reduce pollutants in wastewater. This study aims to determine the effectiveness of kepok banana peel and moringa seeds as bio-coagulants in tofu wastewater treatment. The research tested various doses of the bio-coagulants from kepok banana peel and moringa seeds, specifically 2, 3, 4, 5, and 6 g/L, with a sedimentation time of 24 hours. Bio-coagulant (moringa seed) usage in a dose of 4 g/L has the highest impact on tofu wastewater. Moringa seeds bio-coagulant increased pH to 4.48, turbidity reduction was 90.67%, COD reduction was 75%, and the TSS reduction was 98.02%. Keywords: Biocoagulant; Tofu Wastewater; Kepok Banana Peel; Moringa Seed